A Rare Case of Cervical Solitary Fibrous Tumor in a Pediatric Patient: Case Report and Literature Review - Eleonora Becattini; Lorenzo Sgarbanti; Giuseppina Bevacqua; Valentina Grespi; Carlo Conti (NeuroSci)
Solitary fibrous tumors (SFTs) are rare mesenchymal neoplasms of fibroblastic origin. In this study, we report a rare case of cervical SFT in a pediatric patient, a rare phenomenon since the incidence is particularly rare in pediatric patients according to the literature. Typical radiological features of the lesion may lead to misdiagnosis. Image study and immunohistochemistry are crucial for its correct diagnosis. Their imaging characteristics often resemble meningiomas or schwannomas, making differential diagnosis challenging. Immunohistochemical markers such as CD34 and STAT6 remain essential for definitive diagnosis.